A comparison of the effects of human and ovine corticotropin-releasing hormone on the pituitary-adrenal axis. - Trainer, P; Faria, M; Newell-Price, J; Browne, P; Kopelman, P; Coy, D; Besser, G; Grossman, AB (1995)
To compare the clinical efficacy of ovine and human sequence corticotropin-releasing hormone (CRH), we examined the effects of both peptides on ACTH and cortisol secretion in normal human volunteers, obese subjects, and patients with pituitary-dependent (Cushing's disease) and adrenal-dependent Cushing's syndrome. All subjects in each group were studied twice in random order. One hundred micrograms of CRH were administered as an iv bolus through an in-dwelling forearm cannula at 0930 h, and thereafter, blood was drawn every 15 min for 2 h for the measurement of ACTH and cortisol. In the normal subjects, the peak ACTH, peak incremental ACTH, and mean area under the curve after CRH treatment were greater with ovine CRH than human CRH, although there was no difference in the cortisol response, however it was analyzed. There was no difference in the ACTH or cortisol response to the two preparations in the obese subjects, and no significant difference was found, for either cortisol or ACTH, between obese subjects and normal volunteers. With both varieties of CRH, Cushing's disease resulted in greater responses for ACTH and cortisol than those seen in the other 2 groups (P < 0.001 for all comparisons), but there was no difference between the sequences. However, a significant cortisol response, defined as an increase of greater than 4 times the coefficient of variation of the assay (24%), was seen in all 10 Cushing's patients with human CRH, but in only 8 with ovine CRH. In 3 patients with adrenal tumors, serum cortisol did not change after the administration of either preparation, whereas plasma ACTH remained undetectable throughout the study. We suggest that although ovine sequence CRH causes more prolonged and greater ACTH, and possibly cortisol, secretion compared to human CRH, the discriminatory value of the CRH test, in terms of either the diagnosis or differential diagnosis of Cushing's syndrome, is comparable for the two peptide sequences.